Research on the Design and Application of Power Management Integrated Circuits - Huang, Tao (International Journal of Mechanical and Electrical Engineering, 2025)
With the rapid development of electronic devices toward miniaturization, low power consumption, and high integration, power management integrated circuits (PMICs), as the "energy hub" of electronic systems, have a significant impact on the energy efficiency, reliability, and battery life of end devices. This paper examines the core design and practical applications of PMICs. First, it identifies the key technical requirements for PMICs in different scenarios. It then conducts an in-depth analysis of implementation paths for topology design, energy efficiency optimization techniques, reliability protection, and electromagnetic compatibility (EMC) optimization. The feasibility of these technologies is verified by integrating mass production solutions from manufacturers such as Texas Instruments and Infineon. At the application level, this paper focuses on practical cases of PMICs in consumer electronics, new energy, industrial control, and automotive electronics. Finally, it summarizes the challenges currently faced by PMIC design, such as wide-bandgap semiconductor adaptation and high-integration heat dissipation, and looks forward to the development trend of intelligent and highly integrated PMICs. This research demonstrates that PMIC design must be guided by scenario requirements, achieving a balance between energy efficiency, reliability, and cost through the coordinated efforts of multiple technologies. Its expanded application will further promote the greener and more efficient development of the electronic information industry and the new energy sector.